Effect of Titanium Dioxide on Material Properties for Renewable Rapeseed and Sunflower Polyurethane - Mohd Rus, A.Z. (International Journal of Integrated Engineering, 2009)
Polyurethanes (PUs) have been synthesised successfully from renewable resources namely as rapeseed and sunflower oil using 4,4’-methylen-bis-(phenylisocyanate) (MDI) as the cross-linking agent. The mechanical property of these materials was observed in the Dynamic Mechanical Thermal Analysis (DMTA) test. A high tan delta peak is essential for a good damping material. These PUs can be strongly influenced on the addition of small (2.5-10) percentages of titanium dioxide, TiO2, e.g. the damping was improved on adding TiO2. Upon UV-induced aging, two important changes occur as observed in mechanical damping, such as a decrease in the height of the tan delta peak and a shift of the temperature of the tan delta peak to higher values with increased irradiation time. The loss tan delta peaks for the rapeseed-based PU loaded with 2.5, 5, 7.5, 10% of TiO2 were 0.58, 0.6, 0.68, and 0.71 respectively as compared with neat RSPU at only 0.43. These data show that the damping ability is enhanced through the introduction of TiO2 into the polymer. By doping with TiO2, the mechanical or physical properties of these PUs can be altered systematically, such as to get progressive increases in its stiffness and damping property.